1H‐NMR and isotopic fingerprinting of olive oil and its unsaponifiable fraction: Geographical origin of virgin olive oils by pattern recognition. Issue 12 (29th April 2015) - Alonso‐Salces, Rosa M.; Segebarth, Nicolas; Garmón‐Lobato, Sergio; Holland, Margaret V.; Moreno‐Rojas, Jose M.; Fernández‐Pierna, Juan A.; Baeten, Vincent; Fuselli, Sandra R.; Gallo, Blanca; Berrueta, Luis Angel; Reniero, Fabiano; Guillou, Claude; et al.
Abstract : 1 H‐NMR spectral data and H and C isotope abundances of virgin olive oils (VOOs) and their unsaponifiable fractions were analyzed by pattern recognition techniques, such as principal component analysis (PCA) and partial‐least squares discriminant analysis (PLS‐DA). The aim was to develop chemical tools for the authentication of VOOs according to their geographical origin or protected designation of origin (PDO), as well as to detect the mislabeling of the provenance of VOOs, at the regional or national level, or the mislabeling of non‐PDO oils as PDO VOOs. The relationship between stable isotope abundances of the VOOs and their unsaponifiable fractions and the latitude of the VOO geographical origin was confirmed, but these criteria were not completely discriminant to differentiate VOOs according to their geographical origin. However, δ 2 H and/or δ 13 C data provided complementary geographical information to 1 H‐NMR data in the PLS‐DA binary classification models afforded for VOOs from Greece, Spain, Italy, Izmir (Turkey), Crete (Greece), and the PDOs Riviera Ligure (Italy) and Huile d'olive d'Aix−en−Provence (France). 2 H/ 1 H and 13 C/ 12 C ratios of the unsaponifiable fractions of VOOs are reported here for the first time. The present approach for PDO Riviera Ligure VOOs, based on 1 H‐NMR data and C isotope abundance of the bulk oil and its unsaponifiable fraction, outperformed the previously reported classification models. Moreover, the PLS‐DA models to authenticate VOOs from Greece and detect non‐Greek VOOs achieved over 93% of correct predictions. Practical applications: The research can be applied in the protection of consumers and honest producers and retailers, and provides potential tools for antifraud authorities and regulatory bodies, which face the challenge of detecting fraudulent practices that do not comply with EU regulations in the trade of VOOs, such as the mislabeling of VOOs produced in a certain geographical origin [Commission Implementing Regulation (EC) no 29/2012 and Commission Implementing Regulation (EC) no 1335/2013] and/or under specific EU quality schemes, named PDO or PGI [Council Regulation (EC) no 510/2006]. 1 H‐NMR spectral data and H and C isotope abundances of virgin olive oils (VOOs) and their unsaponifiable fractions were analyzed by pattern recognition techniques, in order to develop chemical tools for the authentication of VOOs according to their geographical origin or protected designation of origin (PDO), as well as to detect the mislabeling of the provenance of VOOs, at the regional or national level, or the mislabeling of non‐PDO oils as PDO VOOs. Abstract : 1 H‐NMR spectral data and H and C isotope abundances of virgin olive oils (VOOs) and their unsaponifiable fractions were analyzed by pattern recognition techniques, in order to develop chemical tools for the authentication of VOOs according to their geographical origin or protected designation of origin (PDO), as well as to detect the mislabeling of the provenance of VOOs, at the regional or national level, or the mislabeling of non‐PDO oils as PDO VOOs.